The Analysis of the Effectiveness of Jamsostek Mobile Integration in Increasing Settlement of Old Age Security Claims - Moeda, Fadillah; Yusrizal; Atika (Moneter: Jurnal Keuangan dan Perbankan, 2024)
This study seeks to analyze the effectiveness of Jamsostek Mobile integration in increasing the settlement of Old Age Insurance (JHT) claims at BPJS Employment Tanjung Morawa Branch. This research uses quantitative methods with data collection techniques through questionnaires distributed to BPJS Employment participants who use Jamsostek Mobile. Data was analyzed using the SERVQUAL model to measure service quality based on five dimensions, namely physical evidence, immunity, responsiveness, assurance and empathy. Although this application has been launched, participants continue to encounter various issues while using it.Some of the problems that are often faced include difficulties in operating the application, claim settlement times which are still considered long, and participant satisfaction levels that are not yet optimal. The problem that is still occurring currently at BPJS Employment Tanjung Morawa Branch faces an issue with insufficient public awareness about the Jamsostek mobile application, resulting in many people still visiting the office in person, and there are also many people who do not use cell phones, especially elderly workers. Previous research shown that JMO has been effective in disbursing JHT during the pandemic, in fact there are still problems that need to be addressed, especially at BPJS Employment Tanjung Morawa. this research was conducted to analyze the effectiveness of Jamsostek Mobile integration in increasing the settlement of JHT claims at BPJS Employment Tanjung Morawa Branch. To identify the extent to which this application can simplify the claims process, speed up settlement time, and increase participant satisfaction levels. The findings of this study are expected to offer constructive feedback to BPJS Employment, aiding in the enhancement of their service qualitythrough the Jamsostek Mobile application.